Factors influencing plasma concentration of voriconazole and voriconazole- N-oxide in younger adult and elderly patients - Cheng, Lin; Liang, Zaiming; Liu, Fang; Lin, Ling; Zhang, Jiao; Xie, Linli; Yu, Mingjie; Sun, Fengjun (Frontiers in Pharmacology, 2023)
Background: Voriconazole (VCZ) metabolism is influenced by many factors. Identifying independent influencing factors helps optimize VCZ dosing regimens and maintain its trough concentration (C0) in the therapeutic window. Methods: We conducted a prospective study investigating independent factors influencing VCZ C0 and the VCZ C0 to VCZ N-oxide concentration ratio (C0/CN) in younger adults and elderly patients. A stepwise multivariate linear regression model, including the IL-6 inflammatory marker, was used. The receiver operating characteristic (ROC) curve analysis was used to evaluate the predictive effect of the indicator. Results: A total of 463 VCZ C0 were analyzed from 304 patients. In younger adult patients, the independent factors that influenced VCZ C0 were the levels of total bile acid (TBA) and glutamic-pyruvic transaminase (ALT) and the use of proton-pump inhibitors. The independent factors influencing VCZ C0/CN were IL-6, age, direct bilirubin, and TBA. The TBA level was positively associated with VCZ C0 (ρ = 0.176, p = 0.019). VCZ C0 increased significantly when the TBA levels were higher than 10 μmol/L (p = 0.027). ROC curve analysis indicated that when the TBA level ≥4.05 μmol/L, the incidence of a VCZ C0 greater than 5 μg/ml (95% CI = 0.54–0.74) (p = 0.007) increased. In elderly patients, the influencing factors of VCZ C0 were DBIL, albumin, and estimated glomerular filtration rate (eGFR). The independent factors that affected VCZ C0/CN were eGFR, ALT, γ-glutamyl transferase, TBA, and platelet count. TBA levels showed a positive association with VCZ C0 (ρ = 0.204, p = 0.006) and C0/CN (ρ = 0.342, p < 0.001). VCZ C0/CN increased significantly when TBA levels were greater than 10 μmol/L (p = 0.025). ROC curve analysis indicated that when the TBA level ≥14.55 μmol/L, the incidence of a VCZ C0 greater than 5 μg/ml (95% CI = 0.52–0.71) (p = 0.048) increased. Conclusion: TBA level may serve as a novel marker for VCZ metabolism. eGFR and platelet count should also be considered when using VCZ, especially in elderly patients.